The Effects of Motor Expertise on Sensorimotor Rhythm Desynchronization during Execution and Imagery of Sequential Movements. (1st August 2018) - Zabielska-Mendyk, Emilia; Francuz, Piotr; Jaśkiewicz, Marta; Augustynowicz, Paweł
Highlights: Power in alpha and beta decreased with the complexity of performed movement. Previous research showed relation between complexity and power decrease only for alpha. Also, alpha and beta power decreased with the complexity of imagined movement. Motor expertise influenced alpha desynchronization in the motor execution condition. High and low beta components during movement execution had different topography. Abstract: The purpose of the study was to investigate sensorimotor rhythm desynchronization during the performance of a motor execution and motor imagery task of different complexity, while varying motor musical expertise of subjects. We compared EEG patterns of professional pianists and non-pianists, who either executed or imagined finger tapping movements of different complexity. Results show that the power in alpha (8–12 Hz) and beta (13–30 Hz) rhythms decreases with the complexity of both performed and imagined movements. Motor expertise influenced alpha rhythm desynchronization in the motor execution task – in the group of pianists there were differences in alpha power decrease depending on the complexity of the performed movement. There was no such relationship among non-pianists. In the imagery task, there was a tendency toward an interaction of motor expertise and low and high alpha rhythm components. In the beta band, there was an interaction of frequency and area of the skull occurring in the movement execution condition – high and low beta rhythm components had different topography.